Wood Ash Liquid Fertilizer as Sustainable Soil Nutritional Supplement Modulates Changes on Growth and Fruits Nutritional Compositions of Capsicum frutescens L. - Racheal Tope-akinyetun; Zainab Mustapha; Musa Hussaini; Temitayo Kelani; Anthony Ojewumi (Research in Agricultural Sciences)
The use of plant-derived fertilizers is a promising approach towards sustainable crop production. This study exploited supplementary effects of 100, 75, 50, and 25% wood ash liquid fertilizer (WALF) on the growth and fruit nutritional contents of Capsicum frutescens. Ordinary water served as control. Agronomical, physiological, and fruit nutritional parameters of the pepper were determined. Higher plant height (25.17 cm) was observed in pepper seedlings sprayed with 25% WALF while several leaves (71.20), leaf area (100.62 cm2), specific leaf area (67.14 m2kg-1), and leaf area index (0.31 m2m-2) were higher (p<.05) in pepper treated with 50% WALF compared with other treatments. Higher net assimilation rate (0.0078 gm-2day-1) and leaf area ratio (0.07 m2kg-1) were observed in pepper sprayed with 100 % the treatment as well as the relative growth rate (0.05 mg-1day-1) of C. frutescens spayed with 75 % WALF. 50% WALF produced the highest number of fruits (38). Also, vitamin A (64.01 mg/100g), vitamin B3 (1.73 mg/100g), vitamin B5 (1.30 mg/100g), vitamin B6 (0.27 mg/100g) were observed in the fruits of pepper spayed with 50% WALF. Furthermore, sodium (11.17mg/100g), potassium (363.92 mg/100g), calcium (108.14 mg/100g), and magnesium (58.11 mg/100g) as well as moisture (68.32 %), fat (2.77 %), ash (3.55 %), crude fiber (2.49 %), crude protein (4.43%) and carbohydrate (9.20%) higher in the fruits of C. frutescens treated with 50% WALF. In conclusion, 50% WALF better enhanced the growth, yield, and nutritional quality of C. frutescens fruits.